Pomen prometa za oblikovanje prostora in regije - Kozina, Jani (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
The paper presents the meaning of transport for shaping space and region as one of the most significant spatial structures on the Earthćs surface. After the theoretical conceptualization of transport as a factor for shaping space and verifying of its importance for the shaping of spatial development of Slovenia, in theory we did the same for region and from a practical point of view for the Central Slovenian region.
Keywords: promet; prometna geografija; prostorski razvoj; regionalni razvoj; Slovenia; Slovenija